The syntax of C in Backus-Naur Form

<translation-unit> ::= {<external-declaration>}*

<external-declaration> ::= <function-definition>
                         | <declaration>

<function-definition> ::= {<declaration-specifier>}* <declarator> {<declaration>}* <compound-statement>

<declaration-specifier> ::= <storage-class-specifier>
                          | <type-specifier>
                          | <type-qualifier>

<storage-class-specifier> ::= auto
                            | register
                            | static
                            | extern
                            | typedef

<type-specifier> ::= void
                   | char
                   | short
                   | int
                   | long
                   | float
                   | double
                   | signed
                   | unsigned
                   | <struct-or-union-specifier>
                   | <enum-specifier>
                   | <typedef-name>

<struct-or-union-specifier> ::= <struct-or-union> <identifier> { {<struct-declaration>}+ }
                              | <struct-or-union> { {<struct-declaration>}+ }
                              | <struct-or-union> <identifier>

<struct-or-union> ::= struct
                    | union

<struct-declaration> ::= {<specifier-qualifier>}* <struct-declarator-list>

<specifier-qualifier> ::= <type-specifier>
                        | <type-qualifier>

<struct-declarator-list> ::= <struct-declarator>
                           | <struct-declarator-list> , <struct-declarator>

<struct-declarator> ::= <declarator>
                      | <declarator> : <constant-expression>
                      | : <constant-expression>

<declarator> ::= {<pointer>}? <direct-declarator>

<pointer> ::= * {<type-qualifier>}* {<pointer>}?

<type-qualifier> ::= const
                   | volatile

<direct-declarator> ::= <identifier>
                      | ( <declarator> )
                      | <direct-declarator> [ {<constant-expression>}? ]
                      | <direct-declarator> ( <parameter-type-list> )
                      | <direct-declarator> ( {<identifier>}* )

<constant-expression> ::= <conditional-expression>

<conditional-expression> ::= <logical-or-expression>
                           | <logical-or-expression> ? <expression> : <conditional-expression>

<logical-or-expression> ::= <logical-and-expression>
                          | <logical-or-expression || <logical-and-expression>

<logical-and-expression> ::= <inclusive-or-expression>
                           | <logical-and-expression && <inclusive-or-expression>

<inclusive-or-expression> ::= <exclusive-or-expression>
                            | <inclusive-or-expression> | <exclusive-or-expression>

<exclusive-or-expression> ::= <and-expression>
                            | <exclusive-or-expression> ^ <and-expression>

<and-expression> ::= <equality-expression>
                   | <and-expression> & <equality-expression>

<equality-expression> ::= <relational-expression>
                        | <equality-expression> == <relational-expression>
                        | <equality-expression> != <relational-expression>

<relational-expression> ::= <shift-expression>
                          | <relational-expression> < <shift-expression>
                          | <relational-expression> > <shift-expression>
                          | <relational-expression> <= <shift-expression>
                          | <relational-expression> >= <shift-expression>

<shift-expression> ::= <additive-expression>
                     | <shift-expression> << <additive-expression>
                     | <shift-expression> >> <additive-expression>

<additive-expression> ::= <multiplicative-expression>
                        | <additive-expression> + <multiplicative-expression>
                        | <additive-expression> - <multiplicative-expression>

<multiplicative-expression> ::= <cast-expression>
                              | <multiplicative-expression> * <cast-expression>
                              | <multiplicative-expression> / <cast-expression>
                              | <multiplicative-expression> % <cast-expression>

<cast-expression> ::= <unary-expression>
                    | ( <type-name> ) <cast-expression>

<unary-expression> ::= <postfix-expression>
                     | ++ <unary-expression>
                     | -- <unary-expression>
                     | <unary-operator> <cast-expression>
                     | sizeof <unary-expression>
                     | sizeof <type-name>

<postfix-expression> ::= <primary-expression>
                       | <postfix-expression> [ <expression> ]
                       | <postfix-expression> ( {<assignment-expression>}* )
                       | <postfix-expression> . <identifier>
                       | <postfix-expression> -> <identifier>
                       | <postfix-expression> ++
                       | <postfix-expression> --

<primary-expression> ::= <identifier>
                       | <constant>
                       | <string>
                       | ( <expression> )

<constant> ::= <integer-constant>
             | <character-constant>
             | <floating-constant>
             | <enumeration-constant>

<expression> ::= <assignment-expression>
               | <expression> , <assignment-expression>

<assignment-expression> ::= <conditional-expression>
                          | <unary-expression> <assignment-operator> <assignment-expression>

<assignment-operator> ::= =
                        | *=
                        | /=
                        | %=
                        | +=
                        | -=
                        | <<=
                        | >>=
                        | &=
                        | ^=
                        | |=

<unary-operator> ::= &
                   | *
                   | +
                   | -
                   | ~
                   | !

<type-name> ::= {<specifier-qualifier>}+ {<abstract-declarator>}?

<parameter-type-list> ::= <parameter-list>
                        | <parameter-list> , ...

<parameter-list> ::= <parameter-declaration>
                   | <parameter-list> , <parameter-declaration>

<parameter-declaration> ::= {<declaration-specifier>}+ <declarator>
                          | {<declaration-specifier>}+ <abstract-declarator>
                          | {<declaration-specifier>}+

<abstract-declarator> ::= <pointer>
                        | <pointer> <direct-abstract-declarator>
                        | <direct-abstract-declarator>

<direct-abstract-declarator> ::=  ( <abstract-declarator> )
                               | {<direct-abstract-declarator>}? [ {<constant-expression>}? ]
                               | {<direct-abstract-declarator>}? ( {<parameter-type-list>|? )

<enum-specifier> ::= enum <identifier> { <enumerator-list> }
                   | enum { <enumerator-list> }
                   | enum <identifier>

<enumerator-list> ::= <enumerator>
                    | <enumerator-list> , <enumerator>

<enumerator> ::= <identifier>
               | <identifier> = <constant-expression>

<typedef-name> ::= <identifier>

<declaration> ::=  {<declaration-specifier>}+ {<init-declarator>}* ;

<init-declarator> ::= <declarator>
                    | <declarator> = <initializer>

<initializer> ::= <assignment-expression>
                | { <initializer-list> }
                | { <initializer-list> , }

<initializer-list> ::= <initializer>
                     | <initializer-list> , <initializer>

<compound-statement> ::= { {<declaration>}* {<statement>}* }

<statement> ::= <labeled-statement>
              | <expression-statement>
              | <compound-statement>
              | <selection-statement>
              | <iteration-statement>
              | <jump-statement>

<labeled-statement> ::= <identifier> : <statement>
                      | case <constant-expression> : <statement>
                      | default : <statement>

<expression-statement> ::= {<expression>}? ;

<selection-statement> ::= if ( <expression> ) <statement>
                        | if ( <expression> ) <statement> else <statement>
                        | switch ( <expression> ) <statement>

<iteration-statement> ::= while ( <expression> ) <statement>
                        | do <statement> while ( <expression> ) ;
                        | for ( {<expression>}? ; {<expression>}? ; {<expression>}? ) <statement>

<jump-statement> ::= goto <identifier> ;
                   | continue ;
                   | break ;
                   | return {<expression>}? ;

This grammar was adapted from Section A13 of The C programming language, 2nd edition, by Brian W. Kernighan and Dennis M. Ritchie,Prentice Hall, 1988.